2020
DOI: 10.1515/zna-2020-0054
|View full text |Cite
|
Sign up to set email alerts
|

Peristaltic thrusting of a thermal-viscosity nanofluid through a resilient vertical pipe

Abstract: AbstractIn the article, the effects of the thermal viscosity and magnetohydrodynamic on the peristalsis of nanofluid are analyzed. The dominant neutralization is deduced through long wavelength approximation. The analytical solution of velocity and temperature is extracted by using steady perturbation. The pressure gradient and friction forces are obtained. Numerical results are calculated and contrasted with the debated theoretical results. These results are calculated for var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…Let Ψ(k, y, λ) be the Laplace transform of ψ(k, y, t) with respect to time variable, t. Applying the Laplace transformation to both sides of equation (14) yields…”
Section: Reformulation Of Ibvp Using Fourier and Laplace Integral Tramentioning
confidence: 99%
See 1 more Smart Citation
“…Let Ψ(k, y, λ) be the Laplace transform of ψ(k, y, t) with respect to time variable, t. Applying the Laplace transformation to both sides of equation (14) yields…”
Section: Reformulation Of Ibvp Using Fourier and Laplace Integral Tramentioning
confidence: 99%
“…e model is supposed to be useful in medical pumps for drug delivery systems incorporating nanoparticles. In [14], Abumandour et al analyze the effects of viscosity and magnetohydrodynamics of the peristalsis of nanofluid using both analytical and numerical mathematical tools. e authors of [15], Bhatti et al, provide an analytical study of a model of swimming microorganisms in a non-Newtonian blood-based nanofluid moving along an anisotropically narrowing artery.…”
Section: Introductionmentioning
confidence: 99%
“…In the human body's biological system, to explain blood flow, it is essential to study the variation of viscosity because the viscosity of blood near the peripheral region is found to be less when compared with the core region. Several theoretical and experimental researches on the viscosity dependency of pressure have been published over time, and a thorough analysis of this subject can be found in the work of References [30–37]. However, along with variable viscosity, the variable thermal conductivity depends on temperature, also considered in recent research.…”
Section: Introductionmentioning
confidence: 99%
“…A study carried out by Akbar et al, 29 has elevated the peristaltic flow of nanofluid to a separating tube, which combines the temperature using a homotopy perturbation method. Many important results of peristaltic transport of nanofluids flow can be found in Hayat et al, 30 Ramesh and Prakash, 31 Riaz et al, 32 Abumandour et al, 33 Mekheimer et al, 34 and Ellahi et al 35 Double diffusion of volatility of the separated liquid resting its size is determined by two different substances at different values. Stern 36 confirmed that this arrangement is unstable or weed compaction rises to the ground.…”
Section: Introductionmentioning
confidence: 99%